2009
DOI: 10.1105/tpc.108.065227
|View full text |Cite
|
Sign up to set email alerts
|

Obligate Heterodimerization ofArabidopsisPhytochromes C and E and Interaction with the PIF3 Basic Helix-Loop-Helix Transcription Factor

Abstract: Phytochromes are dimeric chromoproteins that regulate plant responses to red (R) and far-red (FR) light. The Arabidopsis thaliana genome encodes five phytochrome apoproteins: type I phyA mediates responses to FR, and type II phyB-phyE mediate shade avoidance and classical R/FR-reversible responses. In this study, we describe the complete in vivo complement of homodimeric and heterodimeric type II phytochromes. Unexpectedly, phyC and phyE do not homodimerize and are present in seedlings only as heterodimers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
130
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(147 citation statements)
references
References 61 publications
16
130
1
Order By: Relevance
“…We failed repeatedly to confirm the T-DNA insertion in an additional previously reported gnl allele, SALK_021362 (Mara and Irish 2008). ga1 (SALK_109115), gid1abc, pif1, pif3, pif1 pif3, pif1 pif3 pif4 pif5 (pif1345), PIF3:MYC(63), rga-24 gai-t6, and spy-3 mutants were described previously (King et al 2001;Silverstone et al 2007;Willige et al 2007;Leivar et al 2008;Clack et al 2009). …”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We failed repeatedly to confirm the T-DNA insertion in an additional previously reported gnl allele, SALK_021362 (Mara and Irish 2008). ga1 (SALK_109115), gid1abc, pif1, pif3, pif1 pif3, pif1 pif3 pif4 pif5 (pif1345), PIF3:MYC(63), rga-24 gai-t6, and spy-3 mutants were described previously (King et al 2001;Silverstone et al 2007;Willige et al 2007;Leivar et al 2008;Clack et al 2009). …”
Section: Biological Materialsmentioning
confidence: 99%
“…7C; Frazer et al 2004). We then immunoprecipitated PIF3:MYC(6x) to test whether GNC and GNL promoter fragments can be recognized by PIF3, at least when expressed from a highlevel constitutive promoter (Clack et al 2009). Indeed, we found that one predicted element of the GNC promoter as well as three predicted elements of the GNL promoter precipitate with PIF3:MYC(6x) (Fig.…”
Section: Gnc and Gnl Are Target Genes Of Pif Transcription Factorsmentioning
confidence: 99%
“…Type II phys (phyB-E) form homo-and heterodimers that complicate interpretation of phenotypes of loss-offunction phy mutants and of gain-of-function YHB transgenics (Sharrock and Clack, 2004;Clack et al, 2009;Hu et al, 2009). The additive circadian defect of phyABD mutants compared with phyAB has been assumed to indicate an ability of phyD to provide light input into the circadian system in the absence of phyB (Devlin and Kay, 2000).…”
Section: Yhb Influences Clock Gene Expression In the Absence Of Othermentioning
confidence: 99%
“…The ability of phyB-E to form homo-and heterodimers introduces complexity into the interpretation of individual phy mutant phenotypes (Sharrock and Clack, 2004;Clack et al, 2009;Hu et al, 2013). In addition, period length in phyABCDE mutants is modestly sensitive to different fluence rates of red light (Hu et al, 2013), suggesting that metabolic processes may complicate the assessment of the role of Phys in light input to the circadian clock.…”
mentioning
confidence: 99%
See 1 more Smart Citation